Propensity adoption of digital technology among small medium enterprises in the tourism industry/ Fadhilahanim Aryani Abdullah ... [et al.] - Abdullah, Fadhilahanim Aryani; Mohd Yassin, Nurul Hafizah; Hasbollah, Hasif Rafidee; Saidi, Normaizatul Akma; Mohd Radzi, Naziatul Aziah; Hashim, Hazzyati (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2022)
Tourism involves people visiting countries or locations outside of the natural environment for personal or business reasons that encompasses products and services. Thus, these days the tourism industry has developed with innovation with an advancement of data and computerized correspondence innovations. This study meantly to identify the factors that influence technology adoption among SMEs in tourism industry. Data were collected using a structured questionnaire that was sent by email to SMEs in the tourism industry in Kelantan, Malaysia. Participants were selected using a convenience sampling technique. A total of 122 responses were analyzed. SmartPLS version 3.2.8 was used for the analysis. Based on the result, it’s shown that Effort Expectancy, performance expectancy, and social influence had a positive influence on the intention to use digital technology among SMEs in the tourism industry. There is a positive relationship between intention to use and the adoption of digital technology among tourism SMEs. This study also confirms the mediating role of intention to use on the relationship between effort expectancy, performance expectancy, and social influence on the adoption of digital technology among tourism SMEs in Kelantan. Additionally, the limitation of this study can be used as a reference to produce a better study. Thus, this study may become a reference for those in the industry, especially in the tourism industry to consider performance expectancy, effort expectancy, social influence, and behavioral intention on the adoption of digital technology in their business to gain more profit.